Do we need better methods of assessing urethral function: ICI‐RS 2013?. Issue 5 (16th May 2014) - Gammie, Andrew; Bosch, Ruud; Djurhuus, Jens Chr.; Goping, Ing; Kirschner‐Hermanns, Ruth
<x xml:space="preserve">Abstract</x> Aims To assess whether current methods of urethral function assessment are sufficient for clinical requirement. Methods A summary of the debate held at the 2013 meeting of the International Consultation on Incontinence Research Society, with subsequent analysis by the authors. Results All reported methods of assessment were reviewed and a summary of reported efficacy and clinical application for each is given. Every method of assessment has limitations as to its use, and in some cases the methods have yet to be proved reliable. Conclusions A gap exists between clinical requirements and the capacity of current urethral function assessments to assist diagnosis. Recommendations are therefore made for future research topics. Neurourol. Urodynam. 33:587–590, 2014. © 2014 Wiley Periodicals, Inc.